Intra-Articular Injection of Adipose-Derived Stem Cells Ameliorates Pain and Cartilage Anabolism/Catabolism in Osteoarthritis: Preclinical and Clinical Evidences - Yan, Bo; Lv, Shuaijie; Tong, Peijian; Yan, Li; Chen, Zuxiang; Zhou, Li; Yuan, Qiang; Guo, Le; Shan, Letian (Frontiers in Pharmacology, 2022)
Background: Osteoarthritis (OA) is the most common joint disorder, lacking disease-modifying treatments. Adipose-derived mesenchymal stem cells (ADSCs) are adult multipotent stromal cells obtained from fat tissue, which holds great potential in treating OA. This study aimed to evaluate the anti-OA efficacy of ADSCs from preclinical and clinical facets and explore the underlying mechanism of action. Methods: In vivo, a single dose of 5  105 ADSCs was injected into the knee joints of monoiodoacetate-induced OA rat model. The levels of metabolic and hypertrophic molecules (MMP13, Collagen II, Collagen X) of chondrocytes were measured by immunohistochemistry. In vitro, cell viability assay was conducted to detect the proliferation ability of chondrocytes treated with ADSCs conditioned medium (ADSCs-CM). Quantitative real-time polymerase chain reaction and Western blot assays were applied to explore the mechanism of action of ADSCs. Moreover, a retrospective analysis was conducted to determine the clinical efficacy and safety of ADSCs on OA patients. Results: The animal study showed that ADSCs significantly alleviated OA cartilage lesions in rats, as was confirmed by downregulation of the MMP13 and Collagen X and upregulation of the Collagen II. In vitro data showed that ADSCs-CM promoted the proliferation of chondrocytes, and significantly restored the IL-1β-induced abnormal expressions of molecular markers IL-6, Aggrecan, Mmp3, Mmp13, Collagen II, Collagen X, Adamts5, Adamts9, Sox6, and Sox9 in chondrocytes. Such regulatory effects of ADSCs-CM on the proliferation and these anabolic, catabolic, and hypertrophic markers of chondrocytes suggested a paracrine-based mode of action of ADSCs. Furthermore, the clinical data showed that ADSCs reduced pain and repaired cartilage damage in OA patients, with no adverse events. Conclusion: This study demonstrated the anti-OA efficacy, safety, and a paracrine-based mechanism of ADSCs, providing a promising cell-based therapeutic option for OA treatment.